Exploring the governance and implementation of sustainable development initiatives through blockchain technology. (September 2020) - Schulz, Karsten A.; Gstrein, Oskar J.; Zwitter, Andrej J.
Highlights: Selected use cases show that blockchain is not a niche solution, yet global scalability requires innovations in governance and energy efficiency. Blockchain can improve malfunctioning, imbalanced or ineffective services, financing schemes, and infrastructural systems. The use of biometrics raises significant concerns as governance processes must be adapted to technological change to avoid creating new risks. The immutability of decentralized ledgers is problematic from a human rights and privacy perspective. Anticipatory governance can contribute to effective risk management in networked and decentralized governance arrangements. Abstract: Societies at large still grapple to categorize digital space as a phenomenon. At the same time, scientists and developers are searching for innovative methods to better understand how the fundamental shifts caused by digital change will affect the future of humanity over the coming decades. Interdisciplinary governance research at the intersection of technological and environmental foresight is urgently needed to minimize the risks of technological change and explore how digitalization may support, hinder or re-shape sustainability transformations. In this article, we focus on the case of 'blockchain' or distributed-ledger technology (DLT) to investigate how recent digital technologies may support the implementation of sustainable development initiatives. Our investigation is centered on areas of public administration and governance which will most likely see an adoption of DLT over the next two decades, such as digital identity, social service provision, and innovative climate finance. To allow for a meaningful comparison of various use cases, we propose four guiding questions that can help researchers, decision-makers and practitioners to determine whether DLT might be an appropriate choice for the sustainability-related task at hand. Moreover, we illustrate how the initial design and subsequent implementation of DLTs may support more centralized or networked modes of governance.